Persepsi Mahasiswa tentang Keputusan Mahkamah Konstitusi Mengenai Syarat Calon Presiden dan Wakil Presiden - Sitompul, Alfredo (IAI Nasional Laa Roiba Bogor, 2025)
Of the phenomenon associated with the constitutional court's decision on the age of candidates for presidents and vice presidents is considered unconstitutional because it is actually established by the 2017 no. 7 law of 2017 that the eligibility of presidential candidates and vice presidents is at least 40 years old. The study aims to explore and analyze deeply how students view or understand this constitutional court decision and what it does to the political and democratic dynamics in Indonesia. The method used in research is a descriptive qualitative with a data-collecting technique an in-depth interview of a semi structure. The theory used is social perception according to jalaludin rakhmat in order to find out how the student's perception in response to a constitutional court ruling on the terms of candidates for President and vice President at the verdict number 90/puu-xxi/2023. As for the findings of this study, that is, positive and negative perceptions and positive and negative effects.